Risk factors predicting subtypes of physical frailty incidence stratified by musculoskeletal diseases in community‐dwelling older adults: The SONIC study - Ohata, Yuka; Godai, Kayo; Kabayama, Mai; Kido, Michiko; Akagi, Yuya; Tseng, Winston; Maus, Marlon; Akasaka, Hiroshi; Takami, Yoichi; Yamamoto, Koichi; Gondo, Yasuyuki; Yasumoto, Saori; et al. (Geriatrics & Gerontology International, 2024)
Aim This study aims to identify the key risk factors that lead to subtypes of physical frailty assessed by walking speed and grip strength among community‐dwelling Japanese individuals, stratified by the presence of musculoskeletal diseases (MSDs) and age group. Methods We included 302 participants aged 70 or 80 years who did not exhibit subtypes of physical frailty at baseline through the Septuagenarians, Octogenarians, Nonagenarians, Investigation with Centenarians (SONIC) study. Our study was a longitudinal study. The outcome was the incidence of subtypes of physical frailty after 3 years. Subtypes of physical frailty were defined as a weak grip strength or slow walking speed, or both, based on the Japanese version of the Cardiovascular Health Study Index. The risk factors for subtypes of physical frailty incidence were examined by age group and MSD, using multivariate logistic regressions. Results Of the 302 participants, 110 (36.4%) had MSD. Those with MSD were significantly more likely to have subtypes of physical frailty after 3 years compared with those without MSD. Among all participants, older age was a risk factor of subtypes of physical frailty (P < 0.05). Without MSD, older age and dissatisfied financial status were risk factors (P < 0.05). With MSD, older age was a risk factor (P < 0.05). By age group, in individuals aged 70 years old, a dissatisfied financial status was a risk factor for those without MSD (P < 0.05), and a higher BMI was one for those with MSD (P < 0.05). Conclusions Older age was a risk factor for subtypes of physical frailty, but other risk factors differed according to the presence of MSD and age. Geriatr Gerontol Int 2024; 24: 797–805. Older age was a risk factor for subtypes of physical frailty assessed by walking speed and grip strength, but other risk factors differed according to the presence of musculoskeletal diseases (MSDs) and age. Preventive care for physical frailty in older adults should consider age and the presence of MSD.